An electron deficiency strategy for enhancing hydrogen evolution on CoP nano-electrocatalysts. (August 2018) - Liao, Hanbin; Sun, Yuanmiao; Dai, Chencheng; Du, Yonghua; Xi, Shibo; Liu, Fei; Yu, Linghui; Yang, Ziyu; Hou, Yanglong; Fisher, Adrian C.; Li, Shuzhou; Xu, Zhichuan J.
Abstract: Optimizing the hydrogen adsorption on electrodes is one of the most effective strategies to promote the hydrogen evolution reaction (HER). In recent years, cobalt phosphides (CoP) have been identified as a promising catalyst for HER in acid. However, the hydrogen adsorption on CoP is strong and a considerable overpotential has to be applied to enable HER. Here, we report a strategy to weaken the hydrogen adsorption on CoP through an electron deficiency in CoP induced by Au@CoP core/shell structure. A weakened hydrogen adsorption is confirmed by the density functional theory (DFT) calculation. Au@CoP gave an overpotential ( η ) of 160 mV at the current density of 1 mA cm −2 CoP, which is about 50 mV less than pure CoP. It also exhibited a turn-over frequency (TOF) value of 0.68 s −1 per active site at η = 150 mV, which is more than 4 times higher than CoP. The strategy reported here holds potential to be extended to other electrodes for optimizing their hydrogen adsorption for HER. Graphical abstract: fx1 Highlights: Au@CoP core/shell nanoparticles were successfully synthesized through a multi-step high-temperature liquid method. Electron transfer from CoP shell to Au core was verified by XPS and in-situ XANES results. Au metal as core modulate the hydrogen adsorption free energy of CoP shell to enhance its HER performance. This work represents a strategy for designing HER electrocatalyst.